Growth variables, yield and nitrogen fixation of bambara groundnut (Vigna subterranea L. Verdc.) landraces at different rates of Christmas Island Rock Phosphate and rice biochar on tropical acid soils. - Musa, Mukhtar (2017)
Bambara groundnut presents a great adaptation potential for mitigating climate change and as a potential alternative crop for the future in its production regions and beyond. Experiments were conducted at the Field Research Centre of the Crops for the Future and the Screenhouse of the University of Nottingham Malaysia Campus to determine the growth variables, yield and nitrogen fixation of Bambara groundnut landraces at different rates of Christmas Island Rock Phosphate and rice biochar in the study area. The treatments consisted of three Bambara groundnut landraces [Ex-Sokoto, Kaaro and NN-1, for which two (Ex-Sokoto and Kaaro) were maintained after the first experiment], two biochar levels (0 and 10 t ha-1) and four levels of rock phosphate (0, 20, 40 and 60 kg P2O5 ha-1, the equivalent of 0, 555.6, 1111.1 and 1666.7 kg ha-1 Christmas Island Rock Phosphate). The treatments in experiment 1 and 3 were laid out in a randomized complete block design (RCBD) replicated three times, whereas experiment 2 was laid out in a completely randomized design (CRD) replicated three times. For all the experiments, data were collected on growth, yield and nitrogen fixation of the crop. The results obtained revealed grain yield and N fixed ranging from 703-2256 kg ha-1 and 32-81 kg ha-1, respectively in experiment 1, 13.2-18.0 g plant-1 and 587-894 mg plant-1, respectively in experiment 2 and 891-1220 kg ha-1 and 101.6-103.4 kg ha-1, respectively in experiment 3, which are comparable to the yields obtained in other regions. Hence, Bambara groundnut can adapt to the tropical acid soil and the growing conditions in the study area. The two field experiments confirm Ex-Sokoto landrace to perform better in the study area in terms of yield than Kaaro landrace. Growing Bambara groundnut and returning the residues (haulm + shells) back to the soil resulted in net addition of N to the soil in the range of 1 to 25.6 kg ha-1, 150-261 mg plant-1 and 63.3-74.1 kg ha-1 observed in experiment 1, 2 and 3, respectively. Application of biochar increased the yield and nitrogen fixation of the crop in the study area. However, the effect of rock phosphate application on the yield and N fixation of the crop was only observed in the screenhouse studies and was optimum at the application rate of 40 kg P2O5 ha-1 (0.56 g kg-1 soil). Thus, Ex-Sokoto landrace could be recommended for grain yield in the study area. Application of biochar at 10 t ha-1 alone was optimum for increased yield of the crop. The implication of the study is that farmers in the study area could apply 10 t ha-1 of biochar on Ex-Sokoto landrace to enhance the yield of the crop.